2012
DOI: 10.1371/journal.pone.0032659
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Mechanistic Investigation of the Arrhythmogenic Role of the Late Sodium Current in Human Heart Failure

Abstract: Heart failure constitutes a major public health problem worldwide. The electrophysiological remodeling of failing hearts sets the stage for malignant arrhythmias, in which the role of the late Na+ current (INaL) is relevant and is currently under investigation. In this study we examined the role of INaL in the electrophysiological phenotype of ventricular myocytes, and its proarrhythmic effects in the failing heart. A model for cellular heart failure was proposed using a modified version of Grandi et al. model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 73 publications
3
75
0
Order By: Relevance
“…In control conditions, GS967 had a slight tendency to decrease APD, with the effect being larger for APD 50 than for APD 90 . 10 There is also ample experimental and theoretical evidence that I NaL enhancement can have opposite pro-arrhtyhmic effects, including an increase of triangulation, 54 reverse rate-dependence of APD prolongation measured in transgenic mice with LQT3 48 or the peak to end interval of the T-wave, which closely approximates TDR, in rabbit ventricular wedges. 5 Perhaps more importantly, many experimental studies have shown that inhibition of I NaL can markedly reduce the risk of drug-induced TdP, e.g., by I Kr blockers.…”
Section: Discussionmentioning
confidence: 99%
“…In control conditions, GS967 had a slight tendency to decrease APD, with the effect being larger for APD 50 than for APD 90 . 10 There is also ample experimental and theoretical evidence that I NaL enhancement can have opposite pro-arrhtyhmic effects, including an increase of triangulation, 54 reverse rate-dependence of APD prolongation measured in transgenic mice with LQT3 48 or the peak to end interval of the T-wave, which closely approximates TDR, in rabbit ventricular wedges. 5 Perhaps more importantly, many experimental studies have shown that inhibition of I NaL can markedly reduce the risk of drug-induced TdP, e.g., by I Kr blockers.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the different Na + flux pathways further suggested that the reduced Na/K flux during acute myocardial ischemia plays the largest role in exacerbated Na + overload during reperfusion, and therefore in the possible development of reperfusion injury [54]. Mechanistic investigations using computational models have also evidenced that intracellular Na + accumulation in heart failure is mainly driven by the electrophysiological remodeling of the Na/K pump current, consequently contributing to the deregulation of intracellular Ca 2+ homeostasis in the failing cardiac myocytes [50,67].…”
Section: Multi-scale Studies Of Na/k Pump Regulation Of Cardiac Repolmentioning
confidence: 99%
“…The contribution of BM and LSM to INa,L is equal at the beginning of this phase, then monotonic reduction of BM leaves LSM the only gating mode shaping the plateau sodium current. Shifts in the relative magnitudes of the different gating modes caused by channel mutations or pathologic conditions have been implicated in cardiac electric disorders [33][34][35][36][37][38][39][40][41][42]. Targeted pharmacological modulation of different gating modes is hoped to exert cardioprotective and antiarrhythmic effects [43][44][45] .…”
Section: Brief Historical Remarks On Cardiac Late Sodium Currentmentioning
confidence: 99%
“…It is now well established that the upregulation of INa,L results in pathologic cardiac function including contractile dysfunction, arrhythmia and structural heart disease [5,6,41,44,57,77,100]. There are several conditions (mutation, hypoxia, ischemia, carbon monoxide, CaMKII or angiotensin II activation, etc.)…”
Section: The Plateau Sodium Current In Heart Diseasesmentioning
confidence: 99%
See 1 more Smart Citation